Understanding drivers and barriers for adoption of climate- smart agriculture through a gender lens: Evidence from India - Barooah, Prapti (International Food Policy Research Institute, 2023)
Adoption of potentially beneficial climate-smart agriculture (CSA) practices has been low. There is limited evidence on opportunities for, and constraints to, adopting agricultural practices to respond to climate change among smallholder farmers, particularly women farmers. Furthermore, CSA is criticized for neglecting existing gender inequities in agriculture and, hence, falling short of responding to the needs of women farmers. This paper draws from quantitative surveys conducted with 2,238 female and 811 male farmers in Gujarat, a western state in India, to understand their perception of climate change and experience with climate shocks; and to assess factors that influence awareness and adoption of CSA practices among women and men. We use panel data from two data-collection rounds conducted in April to August 2022 and April to June 2023. While men mostly consider agricultural aspects and food security issues as the important consequences of climaterelated uncertainties, women also mention impacts on physical and mental well-being. The education level of the respondent, phone ownership, access to formal sources of extension, access to farm-level electricity connection and irrigation, are positively associated with adoption of CSA practices among women. On the other hand, women belonging to female-headed households are less likely to adopt CSA practices. Risk aversion is negatively correlated with adoption of CSA practices for both men and women. The results can be used by governments, nongovernmental organizations, and other critical stakeholders interested in ensuring equity in adoption of CSA practices, thereby enhancing resilience among farming households in low- and middle-income countries.